Enhancing the Detection of Brucella-Specific CD4+ T Cell Responses in Cattle via in vitro Antigenic Expansion and Restimulation - Boggiatto, Paola M.; Schaut, Robert G.; Olsen, Steven C. (Frontiers in Immunology, 2020)
Bovine brucellosis, cause by infection with Brucella abortus, causes reproductive failure in cattle, has a major economic impact to producers, and as a zoonoses, it is a disease of public health concern. Characterization of the protective immune response against Brucella infection is important to our understanding of disease pathogenesis and for the development of diagnostic assays and vaccines. Most of the knowledge regarding protection against Brucella comes from studies in the murine model, but less is known about the immune responses in cattle. Assessment of antigen-specific T cell frequency and functional phenotype are critical to understand the immune status of the host, characterize mechanisms of protective immunity and immunopathology, and to predict immune protection. The frequency of circulating T cells specific for a particular pathogen is often very low, making analysis of such responses difficult. Our goal was to develop a flow-cytometry based approach to better track Brucella-specific T cell responses. Using peripheral blood mononuclear cells (PMBC) from Brucella abortus strain RB51-vaccinated cattle, we optimized an in vitro stimulation protocol based on a combination of antigen and pan-T cell stimulation. We then assessed RB51-specific T cell responses by concurrently measuring proliferation and cytokine production using flow-cytometry. This methodology enhances the detection of peripheral, Brucella-specific responses in cattle following RB51 vaccination. This protocol is versatile in that it can be modified to fit other in vitro stimulation systems and additional functional or phenotypic parameters can be added for flow cytometric detection and characterization of antigen-specific T cells.